Advances in Fluid Mechanics VII 2008
DOI: 10.2495/afm080081
|View full text |Cite
|
Sign up to set email alerts
|

CFD modeling of turbulent boundary layer flow in passive drag-reducing applications

Abstract: In this paper, the turbulence boundary layer, velocity and skin friction coefficient characteristics of grooved surfaces are studied. Flow over surfaces with transverse square, triangular and semicircular grooves are numerically modeled via the finite volume method. Comparisons are made on the basis of the grooved surfaces' skinfriction coefficient, normalized by that of a smooth surface, with Reynolds number in the vicinity of 2 × 10 6 . Results show that square grooves are superior to the two other groove ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To examine the effect of the surface shape on the friction resistance, Bourisli and Al-Sahhaf (2008) analyzed friction coefficient and velocity by a series of simulation tests using riblets in three different directions, square, triangular and semi-circular. As a result, they found that three of the rough surfaces gave less resistance to smooth surfaces and that the triangular riblets provided the greatest drag reduction [6]. Using the simulation software, El-Samni et al (2007) determined the pressure gradient to compensate for mass flow on smooth sur-faces such as curved surfaces at different protrusions and grooves.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the effect of the surface shape on the friction resistance, Bourisli and Al-Sahhaf (2008) analyzed friction coefficient and velocity by a series of simulation tests using riblets in three different directions, square, triangular and semi-circular. As a result, they found that three of the rough surfaces gave less resistance to smooth surfaces and that the triangular riblets provided the greatest drag reduction [6]. Using the simulation software, El-Samni et al (2007) determined the pressure gradient to compensate for mass flow on smooth sur-faces such as curved surfaces at different protrusions and grooves.…”
Section: Introductionmentioning
confidence: 99%
“…To study the effect of surface shape on frictional resistance, Bourisli and Al-Sahhaf [3] analyzed the friction coefficient and velocity by a series of simulation tests using grooves in surfaces gave the less resistance compared with three different shapes, including square, triangle, and smooth semi-circle. The results showed that all non-smooth surfaces.…”
mentioning
confidence: 99%